2015
DOI: 10.1177/0363546514564151
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative MRI T2 Relaxation Time Evaluation of Knee Cartilage

Abstract: No patient had joint-line tenderness or reported pain or clicking on McMurray test or instability. There were also no statistically significant differences in functional scores or medial or lateral meniscus T2 values among the 3 groups (P > .05 for both). There was a significantly higher articular cartilage T2 value in the medial femorotibial articular cartilage for the MS group (P < .01) and the MR group (P < .05) compared with that of the MI group, while there was no significant difference in articular carti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 29 publications
6
16
1
Order By: Relevance
“…In contrast to the results aforementioned, a recent cohort study involving 62 participants showed no significant correlations between cartilage T2 relaxation times and International Knee Documentation Committee and Tegner Lysholm Scoring Scale outcomes after ACL reconstruction 23 . However, possible differences in the study population, different follow-up periods, and use of different patient-reported outcome measures make it difficult to compare the findings and might explain the discrepancies in the reported results from the previous and the present studies.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…In contrast to the results aforementioned, a recent cohort study involving 62 participants showed no significant correlations between cartilage T2 relaxation times and International Knee Documentation Committee and Tegner Lysholm Scoring Scale outcomes after ACL reconstruction 23 . However, possible differences in the study population, different follow-up periods, and use of different patient-reported outcome measures make it difficult to compare the findings and might explain the discrepancies in the reported results from the previous and the present studies.…”
Section: Discussioncontrasting
confidence: 64%
“…Recent advances in quantitative MRI, such as T1ρ and T2, have been used to assess the biochemical matrix depletion of the cartilage in ACL-deficient and reconstructed knees 8, 21, 22 . However, to date, there has been little to no investigation on determining the relationship between these cartilage imaging techniques and patient-reported outcomes after ACLR 23 . Determining such a relationship may help clinicians provide more accurate functional expectations to patients prior to surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the combined ACLR group exhibited less annual percentage cartilage volume increase than the isolated ACLR group (albeit only results for the lateral tibia reached significance). On face value, these results are somewhat counterintuitive as it was hypothesised (H 2 ) that the combined group would demonstrate a more pronounced cartilage increase than the isolated group given that concomitant meniscal pathology is a primary contributor to knee OA after ACLR [5, 41], and thus likely a contributor to post-ACLR cartilage swelling. An explanation for the paradoxical findings might relate to the fact that cartilage volume change was measured across the entire cartilage plate.…”
Section: Discussionmentioning
confidence: 89%
“…Others reported a decrease in collagen content, but an increase in proteoglycan content in osteoarthritic menisci [ 23 ]. There are some studies, however, that have examined quantitative MRI, such as T2 mapping, as a biomarker for meniscal or cartilage degeneration [ 1 , 30 , 31 , 32 , 33 , 34 , 35 ]. Histological grading has not been performed regularly, but most studies demonstrated that T2 mapping can differentiate between healthy patients and patients with osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%